Water Consumption Diagnostic Tool for Gasoline and Diesel Engines - Amayrah, Mohammad; Khamayseh, Ahmad; Sayarah, Ahmad; Aljabari, Saad (جامعة بوليتكنك فلسطين , كلية الهندسة , ميكانيك, 2017)
The project is aimed to determine the source of water leakage in vehicles, in which the source of lack may be from engine or not, and that by the determination of the percentage of water which goes out with exhaust gases and compare it with the theoretical percentage of water. Therefore, by determining the problem of water leakage in the engine can saving time and effort is utilized. The result of this project is a device that changes the physical state of water vapor in exhaust gases to water by condensation, also it work to calculate the theoretical amount of water that emerged from burning fuel, then compare these values to determine if there is leaking in the engine or not. It found that the water condensation efficiency in gasoline engines higher than in diesel engines, where the efficiency in gasoline engines reached 94% and in diesel engines reached 85% because of many reasons that discussed in the project.
Water Consumption Diagnostic Tool for Gasoline and Diesel Engines
CD30292 , ميكانيك 21/2017 , no of pages70 , in the store
Keywords: Gasoline and Diesel Engines